Antidiabetic Potential of Marine Brown Algae—a Mini Review - Thilina L. Gunathilaka; Kalpa Samarakoon; Pathmasiri Ranasinghe; L. Dinithi C. Peiris (Journal of Diabetes Research)
Marine algae are an important source of bioactive metabolites in drug development and nutraceuticals. Diabetes mellitus is a metabolic disorder and the third leading cause of death worldwide due to lifestyle changes associated with rapid urbanization. Due to the adverse side effects of currently available antidiabetic drugs, search for an effective natural-based antidiabetic drug is important to combat diabetes and its complications. Therefore, in lieu with herbal drug development, it is important to find the potential benefits of seaweeds for the management of type 2 diabetes as they are underexplored yet in Sri Lanka. Among the marine seaweeds, natural bioactive compounds are abundant in brown algae with potentials in application as active ingredients in drug leads and nutraceuticals. Bioactive secondary metabolites are derived from numerous biosynthetic pathways of marine algae which contribute to various chemical and biological properties. Phlorotannins present in marine brown algae exhibited antidiabetic activities through different mechanisms such as the inhibitory effect of enzyme targets mainly by inhibiting the enzymes such as α-amylase, α-glucosidase, angiotensin-converting enzymes (ACE), aldose reductase, dipeptidyl peptidase-4, and protein tyrosine phosphatase 1B (PTP 1B) enzyme. In addition, phlorotannins derived from brown algae have the ability to reduce diabetic complications. Hence, the present review focuses on the different antidiabetic mechanisms of secondary bioactive compounds present in marine brown algae.